Design and implementation of a smart solar tracker using Arduino for enhanced energy efficiency - Saadun, Mohd Noor Asril; Narindra Mohan Kumar, Sarveen; Che Sidik, Nor Azwadi (Penerbit Akademia Baru, 2024)
In the universe of solar energy systems, the quest for enhanced energy efficiency has led to the design and implementation of a Smart Solar Tracker using Arduino. This innovative solution leverages advanced control mechanisms to optimize solar panel orientation dynamically, addressing the inherent challenges posed by varying climatic conditions. Traditionally, solar trackers have faced limitations in adapting to changing weather patterns, impacting energy capture efficiency. The Smart Solar Tracker, outlined in this study, overcomes these challenges by integrating Arduino-based technology, demonstrating a robust and strong approach to solar tracking. The main result presented in this work showcases the superior performance of the Smart Solar Tracker, consistently delivering high and stable voltage outputs even in adverse weather conditions. Shows that the implementation of Arduino-based control systems in solar tracking significantly enhances energy efficiency, ensuring consistent power generation across diverse climatic scenarios. This advancement not only underscores the critical role of technology in optimizing renewable energy systems but also positions the Smart Solar Tracker as a promising solution for reliable and resilient solar energy harvesting. In terms of costing smart solar tracker is 3 times higher compared to traditional solar tracker whereas in terms of efficiency smart solar tracker using Arduino is 10 times which is 100 percentage more efficient compared to traditional solar tracker. The smart solar tracker using Arduino efficiency output was 68% which is the highest compared to both solar tracker which is 5% and 27% over 5 days of reading the Smart Solar Tracker. Comparison shows that the smart solar tracker using Arduino is the most efficient. The findings presented specifically lead the way for the broader integration of advanced control mechanisms in renewable energy infrastructure, fostering sustainability in the face of environmental variability.